Identification of Drainage System Capacity using EPA-SWMM 5.2 Version Modeling in Bastiong Karance, Ternate City - Alhadar, Nabila Islamaiya; Yakan, Annisa Fathi (Fakultas Teknik Universitas Khairun, 2025)
Flooding and waterlogging in Bastiong Karance, Ternate City, are recurring problems during heavy rainfall, primarily due to insufficient drainage capacity and high impervious land use. This study evaluates the performance of the existing drainage system through hydrological and hydraulic modeling using EPA-SWMM 5.2. Ten years of maximum daily rainfall data (2014–2024) were analyzed with Gumbel and Log Pearson Type III distributions to estimate design rainfall, while the Mononobe method was used to derive intensity-duration-frequency (IDF) curves. Field surveys provided drainage geometry, and topography data were obtained from Global Mapper. The study area was divided into seven Sub-Catchments, 13 junctions, 14 conduits, and two outfalls. Simulation results indicated that node JN3 experienced localized flooding for 0.09 hours with a peak discharge of 0.296 m³/s and total volume of 0.055×10⁶ liters. Conduits CN2, CN3, CN8, and CN12 experienced surcharge with exceedance durations of 0.01–0.26 hours. These findings highlight the limitations of the current drainage system in accommodating runoff during a 10-year return period storm. Recommended measures include widening critical conduits, constructing retention ponds, and implementing infiltration-based runoff reduction strategies to mitigate future flood risk.